2021
DOI: 10.1007/s10741-021-10139-0
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomyopathy in the era of precision medicine: latest concepts and developments

Abstract: Dilated cardiomyopathy (DCM) is an umbrella term entailing a wide variety of genetic and non-genetic etiologies, leading to left ventricular systolic dysfunction and dilatation, not explained by abnormal loading conditions or coronary artery disease. The clinical presentation can vary from asymptomatic to heart failure symptoms or sudden cardiac death (SCD) even in previously asymptomatic individuals. In the last 2 decades, there has been striking progress in the understanding of the complex genetic basis of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 182 publications
(260 reference statements)
0
59
0
18
Order By: Relevance
“…Among these, dilated cardiomyopathy (DCM) has been estimated between 1 in 250 to 2,500 of the general population ( Hershberger et al, 2013 ). More than 50 genes have been associated with familial DCM encoding sarcomeric, cytoskeletal, nuclear and plasma membrane proteins ( Mestroni et al, 2014 ; Orphanou et al, 2021 ). A prominent locus for familial DCM is LMNA , encoding lamin A and C (lamin A/C; McNally and Mestroni, 2017 ; Peters et al, 2019 ; Schultheiss et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, dilated cardiomyopathy (DCM) has been estimated between 1 in 250 to 2,500 of the general population ( Hershberger et al, 2013 ). More than 50 genes have been associated with familial DCM encoding sarcomeric, cytoskeletal, nuclear and plasma membrane proteins ( Mestroni et al, 2014 ; Orphanou et al, 2021 ). A prominent locus for familial DCM is LMNA , encoding lamin A and C (lamin A/C; McNally and Mestroni, 2017 ; Peters et al, 2019 ; Schultheiss et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…BAG3 is a heat shock protein (HSP) co-chaperone that induces degradation through autophagy [ 12 ]. It is determined that BAG3 is essential for the normal production of filamin and is responsible of myocyte contraction [ 3 ]. This protein plays an important role in the heart, are released during cellular stress and their role is to stimulate the repair and degradation of protein aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed in other studies; recently, a retrospective study showed that mutations in the BAG3 gene due to DCM were mostly associated with early onset and rapid progression of the heart failure. Furthermore, the response to treatment in this gene mutation seemed less effective than on other genetic forms of DCM [ 3 ]. Therefore, our patient is particularly at an increased risk of adverse outcomes due to risk factors, such as male sex, young age, decreased LV systolic function, and LV dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of the affected pathways adds to the complexity of DCM pathogenesis and counts for the heterogeneity in phenotype expression. Sarcomeric DCM mutations include myosin, actin, titin, troponin, and tropomyosin [ 23 ].…”
Section: Classificationmentioning
confidence: 99%